2001
DOI: 10.1128/jvi.75.14.6321-6328.2001
|View full text |Cite
|
Sign up to set email alerts
|

YADD Mutants of Human Immunodeficiency Virus Type 1 and Moloney Murine Leukemia Virus Reverse Transcriptase Are Resistant to Lamivudine Triphosphate (3TCTP) In Vitro

Abstract: When human immunodeficiency virus type 1 (HIV-1) is selected for resistance to 3TC, the methionine normally present at position 184 is replaced by valine or isoleucine. Position 184 is the X of the conserved YXDD motif; positions 185 and 186 form part of the triad of aspartic acids at the polymerase active site. Structural and biochemical analysis of 3TC-resistant HIV-1 reverse transcriptase (RT) led to a model in which a ␤-branched amino acid at position 184 would act as a steric gate. Normal deoxynucleoside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 30 publications
2
31
0
Order By: Relevance
“…Steric hindrance between the side chains of the â-branched amino acids valine, isoleucine and threonine in the YMDD motif with the oxathiolane ring of lamivudine most likely accounts for the phenotypic resistance of both viruses [22,23]. This model may be a simplification, as in-vitro studies have shown that, for example, YADD variants of HIV-1 and Moloney murine leukemia virus are also resistant to lamivudine [21]. These authors suggest that other structural changes of the polymerase active site due to the mutation or the repositioning of the complex between the polymerase, the nucleic acid and the dNTP binding site eventually lead to steric hindrance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Steric hindrance between the side chains of the â-branched amino acids valine, isoleucine and threonine in the YMDD motif with the oxathiolane ring of lamivudine most likely accounts for the phenotypic resistance of both viruses [22,23]. This model may be a simplification, as in-vitro studies have shown that, for example, YADD variants of HIV-1 and Moloney murine leukemia virus are also resistant to lamivudine [21]. These authors suggest that other structural changes of the polymerase active site due to the mutation or the repositioning of the complex between the polymerase, the nucleic acid and the dNTP binding site eventually lead to steric hindrance.…”
Section: Discussionmentioning
confidence: 99%
“…There are accumulating data from molecular modelling and biochemical characterisation of variants that give more detailed insight into the mechanism of resistance of HBV and HIV-1 to lamivudine [21][22][23]. Steric hindrance between the side chains of the â-branched amino acids valine, isoleucine and threonine in the YMDD motif with the oxathiolane ring of lamivudine most likely accounts for the phenotypic resistance of both viruses [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…The open reading frames encoding wild-type HIV-1 RT and each of the RT mutants were cloned into a plasmid containing the HIV-1 PR open reading frame as previously described (6). The plasmid is based on the expression vector pT5m and was introduced into the Escherichia coli strain BL21(DE3)(pLysE).…”
Section: Preparation Of Hiv-1 Rtmentioning
confidence: 99%
“…The processivity and primer extension assays have been previously described (6). In brief, for each sample to be assayed, 0.5 l of 1.0 optical density Ϫ47 sequencing primer (New England Biolabs)/ml was 5Ј end labeled with [␥-32 P]ATP and T4 polynucleotide kinase.…”
Section: Preparation Of Hiv-1 Rtmentioning
confidence: 99%
See 1 more Smart Citation